Cyclic stretch of the substratum using a shape-memory alloy induces directional migration in Dictyostelium cells - Yoshiaki Iwadate; Shigehiko Yumura (BioTechniques)
Living cells are constantly subjected to various mechanical stimulations. They must sense the mechanical aspects of their environment and respond appropriately for proper cell function. In general, cells adhere to substrata. Thus, the cells must receive and respond to mechanical stimuli mainly from the substrata. For example, migrating cells can create their own polarity and migrate in a certain direction even in the absence of any attractive substance. In order to generate such polarity, cells must sense mechanical stimuli from the substrata and transduce these stimuli into intracellular signals. To investigate the relationship between signals derived from mechanical stimuli and related cell functions, one of the most commonly used techniques is the application of mechanical stimuli via stretching of elastic substrata. Here, we developed a new stretching device using a shape-memory alloy (SMA). An SMA has three advantages as an actuator of stretching devices: (i) the cost of the SMA required for the device is inexpensive, ∼$30 USD, (ii) the size of an SMA is very small (0.62 mm in diameter and 22 mm in length), and (iii) an SMA does not generate any vibrating noise, which can negatively affect cells. In response to the cyclic stretching by the new stretching device, Dictyostelium discoideum cells migrated perpendicular to the stretching direction and the migrating speed increased significantly. To our knowledge, this is the first report indicating that migrating cells can create their own polarity by the mechanical stimuli from the substrata.